COVID-19 and the future of microfinance: Evidence and insights from Pakistan - Malik, K; Meki, M; Morduch, J; Ogden, T; Quinn, S; Said, F (Oxford University Press, 2020)
The COVID-19 pandemic threatens lives and livelihoods, and, with that, has created immediate challenges for institutions that serve affected communities. We focus on implications for local microfinance institutions in Pakistan, a country with a mature microfinance sector, serving a large number of households. The institutions serve populations poorly-served by traditional commercial banks, helping customers invest in microenterprises, save, and maintain liquidity. We report results from ‘rapid response’ phone surveys of about 1,000 microenterprise owners, a survey of about 200 microfinance loan officers, and interviews with regulators and senior representatives of microfinance institutions. We ran these surveys starting about a week after the country went into lockdown to prevent the spread of the novel coronavirus. We find that, on average, week-on-week sales and household income both fell by about 90%. Households’ primary immediate concern in early April became how to secure food. As a result, 70% of the sample of current microfinance borrowers reported that they could not repay their loans; loan officers anticipated a repayment rate of just 34% in April 2020. We build from the results to argue that COVID-19 represents a crisis for microfinance in low-income communities. It is also a chance to consider the future of microfinance, and we suggest insights for policy reform.